Development of NTU quant AI platform - Elangovan Karthikeyan (Nanyang Technological University, 2024)
This report showcases the development of NTU Quant AI, a quantitative trading platform that enables traders to trade across multiple asset classes, in different markets, using a single platform, while leveraging AI capabilities such as smart routing. It highlights the main motivations for this project, which can be attributed to the rise of algorithmic trading today, increasing expectations of traders such as the flexibility to utilise their own strategies, and limitations in existing trading platforms in the market.